La prestación de los servicios en régimen de competencia - Mata Coto, Carlos Alberto (2013)
The current study seeks to make the reader familiar with the changes that have suffered some services that used to be provided by the State, and currently are subject to economic liberalization. In this context, the political, economic and juridical structures have changed in terms of administrative intervention and economic regulation of the services. The analysis is principally based on juridical and factual relations maintained between different actors, and the accuracy of the concepts applying in a regime of competition.